Sequence-based genome-wide association study reveals host genomic regions and candidate genes influencing the fecal microbiota of Holstein cows - L. Brulin; M.-P. Sanchez; Z. Cai; S. Ducrocq; G. Even; S. Martel; S. Merlin; C. Audebert; J. Estellé; G. Sahana; P. Croiseau (Journal of Dairy Science)
ABSTRACT: In recent decades, the digestive tract microbiota of livestock has been extensively studied, revealing associations with host phenotypes, including production- and health-related traits. The effect of host genetics on gut microbes has been documented in several species; however, in dairy cattle, the specific genomic regions that influence microbial communities remain relatively unexplored. This study aimed to conduct a sequence-based GWAS and a gene-based association study to identify the genomic regions and candidate genes affecting fecal microbiota diversity and composition in a population of 1,875 commercial Holstein cows. From the sequence-based GWAS conducted on 116 fecal microbiota taxonomic levels, 6 QTL were significantly associated with the abundances of Paeniclostridium, an unclassified genus from the Paludibacteraceae family, Sutterella, Turicibacter, and Akkermansia genera, as well as the associated family Akkermansiaceae. These QTL explained between 2.0% and 25.5% of the phenotypic variances of the taxa abundances. Conversely, no genomic variants were found significant for either the α- or the β-diversity of the fecal microbiota. A gene-based association study subsequently conducted on the sequence-based GWAS results revealed significant effects of 90 genes across the bovine genome, affecting the relative abundances of some fecal taxa. Many of these genes were located within the major histocompatibility complex and enriched in immune response pathways. By combining GWAS with gene-based association studies, we specifically identified an association between the ABO gene and the fecal abundance of Akkermansia and Akkermansiaceae. The study represents a significant step forward in understanding the genetic determinism of the complex interactions between the fecal microbiota and their host. It provides new insights into the biological mechanisms underlying host-microbiota interaction in dairy cattle and unveils strong associations between host genomic regions and fecal microbiota in a commercial population. This study holds promise for large-scale breeding strategies to shape the fecal microbiota in Holstein cows and benefit from the host-microbiota interactions.